2016
DOI: 10.5812/pedinfect.39477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum 25-Hydroxy Vitamin D Levels in Children with Acute Bronchiolitis

Abstract: Background: According to some reports, 25-hydroxy vitamin D (25 (OH) D) deficiency leads to respiratory diseases. Given the high prevalence of acute bronchiolitis in young infants, the assessment of 25 (OH) D status is very important for this disease. Objectives: This study was conducted to determine the relationship between the serum levels of 25 (OH) D and acute bronchiolitis in young infants. Methods: In the present study, 57 patients with acute bronchiolitis (case control) were compared with 57 healthy chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…We searched PubMed using keywords such as “vitamin D” and “lower respiratory tract infections” or “viral infections,” focusing on studies on pediatric populations, including both observational studies and clinical trials. Numerous studies investigated the association between low levels of 25-hydroxyvitamin D and increased susceptibility to LRTI in childhood, as listed in Table 4 [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ].…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched PubMed using keywords such as “vitamin D” and “lower respiratory tract infections” or “viral infections,” focusing on studies on pediatric populations, including both observational studies and clinical trials. Numerous studies investigated the association between low levels of 25-hydroxyvitamin D and increased susceptibility to LRTI in childhood, as listed in Table 4 [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Some studies showed contrasting evidence and found no difference in vitamin D status in LRTI patients vs. controls [ 129 , 137 , 141 ]. A 2016 study conducted in Hong Kong on children and adults found no significant association between lower levels of vitamin D and higher incidence of influenza virus infections [ 140 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Conversely, a study on children aged 1–25 months admitted to hospital with lower respiratory tract infections (primarily viral bronchiolitis), did not find any association between serum vitamin D levels and the risk of hospitalization [ 5 ]. At last, no significant difference between children aged 1–24 months hospitalized with acute bronchiolitis and controls was highlighted in a recent case-control study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the rates of vitamin D deficiency and insufficiency were high in both groups (25 and 22%, respectively), leading the authors to recommend routine screening for vitamin D deficiency in children with LRI, and vitamin D supplementation in all children, especially during the winter months [75]. Similarly, one study in Canada and one in Iran found no significant differences between cases and controls in terms of 25(OH)D serum levels for uncomplicated ALRI (primary viral bronchiolitis) in children less than 2 years old [76,77].…”
Section: Evidencementioning
confidence: 97%